Cover Image, Volume 38, Issue 10. Issue 10 (14th September 2017) - Oprescu, Stephanie N.; Chepa‐Lotrea, Xenia; Takase, Ryuichi; Golas, Gretchen; Markello, Thomas C.; Adams, David R.; Toro, Camilo; Gropman, Andrea L.; Hou, Ya‐Ming; Malicdan, May Christine V.; Gahl, William A.; Tifft, Cynthia J.; et al.
Abstract : On the cover : This cover image, by Stephanie N. Oprescu et al., is based on the Research Article Compound heterozygosity for loss‐of‐function GARS variants results in a multisystem developmental syndrome that includes severe growth retardation, Pages 1412–1420. DOI:10.1002/humu.23287 .